Adaptive Power Charge Using PID Controller on DC Load Application - Murdianto, Farid Dwi; Sudiharto, Indhana; Irianto, Irianto; Wulandari, Ayu (Politeknik Negeri Ujung Pandang, 2020)
Battery is a very important necessity as an electrical energy storage for DC load type. However, as electric energy storage, the battery has a limit storage capacity. The battery must be recharged when the electrical energy stored in the battery has been exhausted to keep the DC load in operation. Unfortunately, batteries in different types of DC loads have different voltages and capacities. So for charging the battery also requires a different voltage. While the existing battery charger is generally static specifically for one type of battery. From this problem, the paper proposed an adaptive power charge system. A system that can adaptively charge electrical energy on batteries that have different voltages and capacities through one port. The converter used in this paper is the buck converter to lower the output voltage from the input voltage. The system uses tracking duty cycle to know the type of DC load. After knowing the type of dc load then the system determines the setting point voltage. To keep the output voltage stable, the system uses PID control. With this adaptive power charge, the charging process will be more efficient and multifunction because it can be used for various types of DC load. The system can provide an output voltage of 19 volts when connected to a laptop and provides an output voltage of 5 volts when connected to a mobile phone on setling time 10ms.